2015
DOI: 10.1088/1054-660x/25/8/085004
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of a LG10beam into an optical bottle beam

Abstract: We have demonstrated that a simple diaphragm can play the role of a very cheap reconfigurable diffractive optical element allowing the generation of interesting laser beam patterns. For instance, a truncated Laguerre-Gauss LG 10 beam (one peak surrounded by one ring) can be transformed in the focal plane of a lens into an optical bottle beam (OBB) which consists to a dark (or minimal intensity) region surrounded by higher intensity light in the three principal directions. Depending on the beam truncation, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Various approaches to the generation of LHBs have been proposed since the demonstration of this beam was first realized by using the destructive interference between two light beams at the focus [16]. They were generated by the use of nonparaxial light [17][18][19], holograms [16,20], binary phase plates [21][22][23][24], conical refraction [25][26][27][28][29], a uniaxial crystal [30], partially coherent beams [31,32], a spatial light modulator (SLM) [33], surface plasmon polaritons [34,35], and a photon sieve [36], to form a desirable hollow axial structure. In phase modulation methods, the diffractive optical elements, such as the π-phase plate, are constructed by the binary elements or the binary bitmap of the SLM.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches to the generation of LHBs have been proposed since the demonstration of this beam was first realized by using the destructive interference between two light beams at the focus [16]. They were generated by the use of nonparaxial light [17][18][19], holograms [16,20], binary phase plates [21][22][23][24], conical refraction [25][26][27][28][29], a uniaxial crystal [30], partially coherent beams [31,32], a spatial light modulator (SLM) [33], surface plasmon polaritons [34,35], and a photon sieve [36], to form a desirable hollow axial structure. In phase modulation methods, the diffractive optical elements, such as the π-phase plate, are constructed by the binary elements or the binary bitmap of the SLM.…”
Section: Introductionmentioning
confidence: 99%
“…the Gaussian LG 00 beam. Nowadays, we are witnessing a new upsurge of investigations on highorder transverse modes in lasers [15][16][17][18][19][20][21][22][23], and specific applications such as particle trapping [24], quantum information [25], optical tweezers [26], and laser beam shaping [27,28]. We can thus legitimately investigate the effects of spherical aberration on the focusing of a high-order transverse mode.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was found that when η + is close to 0.96, the far-field distribution is made up of a flat-top intensity profile [56]. In contrast, when η + is in the range of 67% to 74%, the far-field is a hollow beam or, more precisely, an optical bottle beam [57].…”
Section: Transformation Of a Radial Laguerre-gaussian Lg P0 Beam Into...mentioning
confidence: 99%
“…In order to reshape the LG30 beam into an OBB, + η needed to be close to 67%, and this could be achieved if As a result, the OBB length was found to be 0.8 R z z Δ = , while the same reshaping of the LG10 beam achieved by using a diaphragm gave an OBB length of R z z 6 . 6 = Δ [57].…”
Section: (B) Lg30 Beammentioning
confidence: 99%